HIERARCHY OF HAPPINESS IN AL-SHA’RÂWÎ’S INTERPRETATION OF THE TERM AL-SURÛR FROM THE PERSPECTIVE OF ABRAHAM MASLOW - Putri Alfia Halida (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Happiness is the foremost goal of humans’ in running their activities. Even the fulfillment of the most basic needs is motivated to achieve it. However, the measure of happiness becomes very difficult to determine. In this context, al-Qur'an guides by mentioning various redactions that have the meaning of happiness, such as al-surûr. Therefore, this study aims to find the happiness fulfillment model described in the Qur'an. This study uses the interpretation of al-Sha'rawi, to narrow the scope of meaning, which is considered more relevant to the context of modern society. This research uses a literature study method with data analysis techniques using the approach of Abraham Maslow’s hierarchy of needs. This research concludes that al-Sha’râwî interprets the word al-surûr as happiness in the world and the hereafter. In the world, happiness is achieved by enjoying sensory beauty, while in the afterlife, it will be achieved by behaving obediently in the world. The achievement of happiness is precisely obtained by fulfilling the needs following the hierarchy of happiness. At the early stage, happiness is achieved through theological belief. This belief will lead to sensory happiness in the world. At the uppermost stage, the peak of happiness can only be reached when humans meet their God.